Improved Intelligence, Literacy and Mathematic Skills Following School-Based Intervention for Children in Foster Care - Tordön, Rikard; Bladh, Marie; Sydsjö, Gunilla; Svedin, Carl Göran (Frontiers in Psychology, 2020)
Interventions aimed at improving school performance for children in foster care are few and are not implemented generally. By preventing failure in school, the prospect of reducing the risk for future poor health, substance abuse, unemployment, and other detrimental social conditions are met. This paper focuses on the change of preconditions for compulsory school performance in out-of-home care children, following an intervention called “Skolfam” that aims to improve school performance by individual assessments and school-based interventions. In this study, data were compiled from prospective repeated tests of 475 children in foster care in Sweden. Educational preconditions were analysed for compulsory school performance, such as intelligence (WISC-IV), psychosocial (SDQ) and adaptive behaviour (ABAS-II), literacy (Reading Chains) and mathematical skills (Magne Mathematic Diagnoses) before and after the first two years of the “Skolfam” intervention. All tests were age-standardized and performed by experienced professionals. The results showed improved skills in complex aspects of literacy, mathematics, and cognitive performance, but no improvement in less complex literacy skills, adaptive behaviour or mental health symptoms. In conclusion, higher-order cognitive functions can develop positively when appropriate school support is provided. Affective function, adaptive behaviour, and psychosocial well-being present a more pervasive challenge for children in foster care. Implications for future research, practice in social services, and school is that further development of methods to aid future prospects for children in out-of-home care should aim to improve both cognitive higher-order executive-, and affective functions.